Анализ Дела о Смерти Джамаля Хашогги: Перспективы Международного Права и Государственной Юрисдикции (Analysis of the Jamal Khashoggi Death Case: Perspectives on International Law and State Jurisdiction) - Faris, Dzaka Ashriel; Fadillah, Firman; Machyawaty, Tety (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The case of the murder of Jamal Khashoggi at the Saudi Consulate in Istanbul has drawn the attention of the international community to such important issues of international law as the abuse of diplomatic immunity and State responsibility for human rights violations. This analysis reveals the dynamics of international law and national jurisdiction in relation to crimes committed at diplomatic facilities, which should be protected by diplomatic immunity. The principle of territorial jurisdiction allows Turkey, as a crime scene, to investigate and bring the perpetrators to justice, while Saudi Arabia faces problems in complying with international conventions on law enforcement, fair treatment of foreign citizens and protection of human rights. The Khashoggi case raises questions about the extent to which diplomatic immunity can protect international crimes and how countries can fulfill their obligations under international law without sacrificing sovereignty. The impact of this event on Saudi Arabia's reputation and diplomatic relations is also significant, which has sparked a debate about the role of soft power and ethics in world politics. This study aims to deepen understanding of the challenges in the field of international justice, emphasizing the importance of States complying with existing international standards and responding decisively to the abuse of diplomatic immunity. The study concludes by emphasizing the need to reform international law as a preventive measure against such crimes in the future, while ensuring respect for the principles of justice at all levels.